Spectroscopic observations of the bilobate potentially hazardous asteroid 2014 JO25 from the Asiago 1.22-m telescope. (1st September 2018) - Petropoulou, V.; Lazzarin, M.; Bertini, I.; Ochner, P.; La Forgia, F.; Siviero, A.; Ferri, F.; Naletto, G.
Abstract: The potentially hazardous asteroid (PHA) 2014 JO25 made a close approach to Earth on 19 April 2017 at the distance of 0.0118 AU, giving the opportunity to study its nature with large spatial resolution from ground-based observatories. Radar observations revealed an object with a clear bilobate shape. We aimed at the characterization of the surface properties of the object, the determination of its spectral class and the search for possible surface heterogeneities, possibly linked to the two lobes, during different rotational phases. Fourteen low-resolution spectra were acquired with the Boller & Chivens optical spectrograph mounted on the 1.22–m Asiago telescope. The spectra covered an entire rotation period of the asteroid. Data were reduced using IRAF and analyzed with the M4AST tool to infer the best fit Bus-Demeo taxonomy type. We found the asteroid belonging to the S/Q complex of silicaceous asteroids, complex comprising the vast majority of NEAs. This is the tenth bilobate NEA to be taxonomically classified and only the seventh bilobate PHA. We found no clear proof of surface heterogeneity, but there is an interestingvariation in the best spectral match which appears to be synchronous with the rotation period of the object. Highlights: We observed the PHA 2014 JO25 on 20 April 2017 at the distance of ~0.03 AU. We obtained 14 low-resolution spectra from 1.22--m Asiago telescope. We found the asteroid belonging to the S/Q complex of silicaceous asteroids. It is the tenth bilobate NEA taxonomically classified and seventh bilobate PHA. We found an interesting periodicity of spectral slope with rotation period.